An observational study of dental abnormalities in the primary teeth - Andréia Drawanz Hartwig; Marina Sousa Azevedo; Laís Anschau Pauli; Katerine Arteiro Jahnecke; Fernanda Gerardo Pappen; Ana Regina Romano (Revista Sul-Brasileira de Odontologia, 2019)
Pregnancy and early childhood are the most critical phases with regard to biological, cognitive, emotional, and social development. Adverse events in these periods of life may be related to alterations in dental development, including alterations in size, shape and mineralization. Objective: To evaluate the frequency of dental abnormalities and the factors associated with the developmental defects of the enamel in primary teeth. Material and methods: Information about family income, maternal education level, preterm birth, and hospitalization history up to 11 months of age were collected from the dental records of 544 children. Clinical examination of the children was performed to investigate abnormalities of tooth number, form, size, and developmental defects of the enamel (DDE). Data were analyzed using χ2 test and Poisson regression. Results: In all, 544 children were evaluated. Sixty children (11.0%) presented some alterations in the primary teeth; and 7.5% showed DDE. Children born preterm were 3.17 times more likely to develop DDE in primary teeth (prevalence ratio – PR = 3.17, 95% confidence interval – 95%CI 1.26–7.98, p = 0.014). Among the alterations of number, 1.7% was hypodontia, and among the abnormalities of shape, 1.7% was fused teeth. Conclusion: The prevalence of dental anomalies in this sample was, in general, expressive. Children born preterm were more vulnerable to present developmental defects of the enamel.